2008
DOI: 10.2741/2775
|View full text |Cite
|
Sign up to set email alerts
|

Factors regulating apoptosis and homeostasis of CD4+CD25highFOXP3+ regulatory T cells are new therapeutic targets

Abstract: CD4+ CD25(high) Foxp3+ regulatory T cells (Tregs), as an active mechanism of immune suppression, have been targeted due to their tremendous therapeutic potentials to prevent autoimmune diseases, transplant rejection, and to inhibit progression of tumors and chronic viral diseases. In last twelve years, substantial molecular differences between homeostasis of Tregs and that of other subsets of T cells and some factors specific in regulation of Treg survival have been characterized. In this overview we focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 251 publications
4
73
0
Order By: Relevance
“…Preliminary data suggesting that dietary modification may reduce the levels of oxLDL and increase the levels of IgM PC antibodies [93] certainly increases the interest in determining whether high levels of IgM mLDL antibodies may have a beneficial effect on the evolution of atherosclerosis. Alternative interventions could involve controlled upregulation of T regulatory cells (Tregs), which has a strong theoretical appeal [94,95], and has been reported as an effective form of manipulation of transplant rejections responses [96], but is a rather distant target at this time. The only practical approach at this time is to reduce the antigenic load, either by dietary modification, or by pharmacological means.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data suggesting that dietary modification may reduce the levels of oxLDL and increase the levels of IgM PC antibodies [93] certainly increases the interest in determining whether high levels of IgM mLDL antibodies may have a beneficial effect on the evolution of atherosclerosis. Alternative interventions could involve controlled upregulation of T regulatory cells (Tregs), which has a strong theoretical appeal [94,95], and has been reported as an effective form of manipulation of transplant rejections responses [96], but is a rather distant target at this time. The only practical approach at this time is to reduce the antigenic load, either by dietary modification, or by pharmacological means.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-2-regulated Treg apoptotic pathways that underlie homeostatic mechanisms of Tregs remain poorly defined. Since homeostasis of Tregs is critical in maintaining immune tolerance and regulation of immune responses, elucidation of Treg-specific apoptotic pathways is significant (15). Our recent report showed that expression of pro-apoptotic protein Bax in Tregs is higher than that in CD4+CD25− T cells in the absence of any stimuli, which may be responsible for higher apoptosis rates of Tregs (10).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that Tregs are highly susceptible to apoptosis (15,34). Since Tregs generate poorly endogenous IL-2(7), Tregs require exogenous IL-2 for survival by expressing high levels of IL-2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…37 Therefore, enhanced recruitment of antitumor effector T lymphocytes to tumor tissue, in addition to inhibition of local regulatory T cells, may be an ideal target for improving cancer immunotherapy. [30][31][32][33][34][38][39][40] Strategies aimed at depletion/functional inhibition of these cells by molecular targeting must maintain a critical balance between tumor immunity and self-tolerance. 34,[41][42][43][44] These immunomodulation pathways may therefore have potential applications in forthcoming treatments of cancer.…”
Section: Regulatory T Cells In Endometrial Cancer/chang Et Almentioning
confidence: 99%